Perspectives on data science for software engineering - Menzies, Tim; Williams, Laurie 1962-; Zimmermann, Thomas (Morgan Kaufmann is an imprint of Elsevier, 2016)
Presenting the best practices of seasoned data miners in software engineering, this book offers unique insights into the wisdom of the communityOCLCbr#92s leaders gathered to share hard-won lessons from the trenches. --
Includes bibliographical references
Keywords: COMPUTERS / General; Software engineering; Datenmanagement; Software Engineering